Complex Analysis of Linguistic Situation and Linguistic Legislation of Post-war Abkhazia: (1993-2012) - Tabidze, Manana; Nachkebia, Merab (Actual Problems of Kartvelology, 2025)
Generally, passing ‘linguistic law’ is connected with critical moments of linguistic situation; correspondingly, in case of absence of these problems, there is no need of the linguistic law; linguistic law poses the need of existence of polylingual society (it should be noted that nowadays there are no more monolingual states in the world), maintenance of linguistic policy, balance and safety of linguistic identity and cultural individuality of several linguistic groups. Each country has its own way of formulating the linguistic law. All linguistic ambitions were put into the linguistic law of the self-declared Republic of Abkhazia. According to this very law, Abkhazian language is the only state language on the Abkhazian ‘territory’. The article analyses the linguistic situation of the last decade in Abkhazia and the reasons that prevented the application of the abovementioned linguistic law.